Blender 3D : designing objects : build your very own stunning characters in Blender from scratch : a course in three modules.: designing objects : build your very own stunning characters in Blender from scratch : a course in three modules. (2016) - Caudron, Romain; Nicq, Pierre-Armand; Valenza, Enrico
No abstract available